STRATEGI PERSONAL BRANDING FIGUR EDUKATIF DI MEDIA SOSIAL - Victoria, Michelle Nathasya; Al Faizzah, Iris Azalea Camilla; Putri, Rizky Aulia (Lentera Jurnal Manajemen, 2025)
This study aims to examine how educational figures apply personal branding strategies on social media, with a primary focus on Jerome Polin, a popular Indonesian student known for his educational and inspirational content across various digital platforms. The research approach employed a systematic literature review, with journals and articles collected through Google Scholar and Research Gate between 2023 and 2025. The findings reveal that Jerome consistently applies Montoya's eight elements of personal branding strategy, including specialization, personality, uniqueness, leadership, visibility, unity, consistency, and good reputation. The content produced is presented in a light and communicative manner, blending education with humor, making it easy for the audience particularly teenagers to understand the educational messages conveyed. Two-way interaction, consistency in themes, and alignment of personal values with the content shared are key to building a personal brand as an intellectual figure who remains humble. Thus, this study demonstrates that social media-based personal branding strategies can be an effective tool in building a strong and credible professional identity, especially for the younger generation in the digital age. Keywords: Personal branding strategy, Educational figure, and Social media